Iron-catalyzed active lipid peroxides drive ultrafast collective cell death in blooming algae - Yinjie Zhu; Xiaoxiong Wang; Yifan Tong; Chengzhen Jia; Huansheng Cao; Hongying Hu; Yi Tao (Science, 2026)
Harmful algal blooms, the most severe ecological hazards worldwide, terminate abruptly within a few days. In this work, we identified that iron-catalyzed active lipid peroxides predominantly trigger individual cell ferroptosis and drive the population collapse of blooming cyanobacteria. We reveal the chronological sequence of labile iron burst, oxidative stress, lipid peroxidation, and cell death during a Microcystis bloom demise event. Dead cells exhibit a nonrandom spatial distribution within colonies. Intensifying lipid peroxidation catalyzed by cellular labile iron generates truncated phospholipids with shortened fatty acyl chains bearing alkyl groups. These active lipid peroxides destabilize plasma membranes and induce nanoscale membrane pore formation, resulting in individual cell ferroptosis and lysis. Oxidized lipids are also released from ferroptotic cells, propagating lipid peroxidation to neighboring cells, thereby spreading death throughout the population.